Dialektika Maqasid as-Syari’ah Dalam Metode Istinbath Hukum Islam - Muh. Muhyiddin; Ibnu Chudzaifah; Afroh Nailil Hikmah (LPPM IAIN Sorong, 2021)
Maqashid as-shari'ah is a new trend in the legal istinbath that is undergoing development in the contemporary era. The development of the method of extracting the source of contemporary Islamic law is now considered more promising as using maqashid as-sharia. As a scientific discipline that is the development of fiqh and fiqh rules, maqashid as-shari'ah is now widely studied by experts in Islamic law more deeply. Benefit as the essence of maqashid as-shari'ah, has urgency in determining Islamic law. Because Islamic law is revealed has the purpose and purpose to realize the benefit of the people both in this world and in the Hereafter. Thus the study of maqashid as-shari'ah has a very important correlation in extracting the source of Islamic law, in other words that the excavation of Islamic law based on benefit still refers to the books of qawaid al-fiqhi and ushul al-fiqh. As for the way used by the scholars' in exploring the benefits there are three methods: bayani method (substantive analysis), qiyasi method (analogy analysis), and istishlahi method (benefit analysis)